Friedman tongue position: Age distribution and relationship to sleep-disordered breathing. Issue 5 (May 2015) - Ingram, David G.; Ruiz, Amanda; Friedman, Norman R.
Abstract Purpose Friedman tongue position (FTP) may play an important role in the evaluation of children with sleep-related breathing disorders (SRBD), but there are no previous data on FTP distribution by age. The objective of the current study was to determine the distribution of FTP by age and examine the relationship between FTP and snoring in children. Methods Prospective cross-sectional study of 199 children (mean age, 6.8 years; 59% male) had tongue position assessed by FTP as part of their clinical examination of the oral cavity during routine ENT visits at a tertiary care children's hospital. The FTP and snoring frequency of participants was examined across the entire age range as well as by comparing those older (middle childhood and above) and younger than 5 years of age. Results Tongue position did not correlate with age or snoring frequency. The proportion of children with FTP III/IV was not significantly different in children younger than five years of age compared to older than five. Habitual snoring was not associated with having a higher FTP. Among children who snored <3 times per week, those who had previously undergone tonsillectomy did have higher FTP compared to those who had not (p = 0.007). BMI-%-for-age was significantly correlated with FTP (p = 0.003). The percent of children having FTP class III/IV differed significantly between ethnicities (22% of whites, 26% of others, 45% of hispanics, 53% of African–Americans; p = 0.011). Inter-rater reliability among pediatric otolaryngologist was excellent (kappa = 0.93, p < 0.001). Conclusions There does not appear to be an association between FTP with age or snoring frequency in children. The excellent inter-rater reliability for FTP among pediatric ENT providers suggests the null findings are not due to rater bias. These findings may serve as an important reference for those studying the role of tongue position in pediatric SRBD and complement previous studies examining FTP among children with known OSA or snoring.